The Therapeutic Use of Ayahuasca - Labate, Beatriz Caiuby; Cavnar, Clancy (Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book presents a series of perspectives on the therapeutic potential of the ritual and clinical use of the Amazonian hallucinogenic brew ayahuasca in the treatment and management of various diseases and ailments, especially its role in psychological well-being and substance dependence. Biomedical and anthropological data on the use of ayahuasca for treating depression, PTSD, and substance dependence in different settings, such as indigenous contexts, neo-shamanic rituals, contemporary therapeutic circles, and in ayahuasca religions, in both South and North America, are presented and critiqued. Though multiple anecdotal reports on the therapeutic use of ayahuasca exist, there has been no systematic and dense reflection on the topic thus far. The book brings the therapeutic use of ayahuasca to a new level of public examination and academic debate. The texts in this volume stimulate discussion on methodological, ethical, and political aspects of research and will enhance the development of this emergent field of studies.